Bone Regeneration Induced by Bone Porcine Block with Bone Marrow Stromal Stem Cells in a Minipig Model of Mandibular "Critical Size" Defect. (2nd May 2017) - Scarano, Antonio; Crincoli, Vito; Di Benedetto, Adriana; Cozzolino, Valerio; Lorusso, Felice; Podaliri Vulpiani, Michele; Grano, Maria; Kalemaj, Zamira; Mori, Giorgio; Grassi, Felice Roberto
Abstract : Introduction . Adding stem cells to biodegradable scaffolds to enhance bone regeneration is a valuable option. Different kinds of stem cells with osteoblastic activity were tested, such as bone marrow stromal stem cells (BMSSCs). Aim . To assess a correct protocol for osteogenic stem cell differentiation, so BMSSCs were seeded on a bone porcine block (BPB). Materials and Methods . Bone marrow from six minipigs was extracted from tibiae and humeri and treated to isolate BMSSCs. After seeding on BPB, critical-size defects were created on each mandible of the minipigs and implanted with BPB and BPB/BMSSCs. After three months, histomorphometric analysis was performed. Results . Histomorphometric analysis provided percentages of the three groups. Tissues present in control defects were 23 ± 2% lamellar bone, 28 ± 1% woven bone, and 56 ± 4% marrow spaces; in BPB defects were 20 ± 5% BPB, 32 ± 2% lamellar bone, 24 ± 1% woven bone, and 28 ± 2% marrow spaces; in BPB/BMSSCs defects were 17 ± 4% BPB/BMSSCs, 42 ± 2% lamellar bone, 12 ± 1% woven bone, and 22 ± 3% marrow spaces. Conclusion . BPB used as a scaffold to induce bone regeneration may benefit from the addition of BDPSCs in the tissue-engineered constructs.